The experience of student self-government in improving the quality of the educational process - Levkin , A.; Levkina , R.; Ryasnyanska , A. (New Collegium, 2020)
The article considers the organization of self-government in higher education. This means voluntary and independent public activities of students to perform the functions of management of higher education, which is determined by its administration. Along with the main tasks of student self-government bodies to ensure and protect the rights and interests of students, it must ensure the performance of duties, influence the discipline and effectiveness of education. Democratic principles of election to these bodies, their effective functioning, and the provision of guarantees are a prerequisite for integration into the Bologna Agreement. The main problems in this are the need to improve the legal framework of the educational process, low financial resources, lack of democratic political culture, the mechanism of interaction with the administration and the passivity of students. Research on the issue shows a lack of awareness of the performance of student government and a low level of trust and authority of its leaders. Instead, the experience of European universities shows in favor of these bodies in solving university-wide cases. Strong material base and financial and legal independence from the administration of the educational institution allow to independently distribute part of the funds for financing grants from student societies and associations at the university. The influence of teachers on the process of formation of future specialists in terms of application of practical experience and modern management technologies is important. Thus there is a formation of the developed personality, stimulation of activity of the future citizen, education of the tolerant interlocutor. The conclusion is made about the importance of student self-government bodies whose activities are aimed at improving the educational process, organizing cooperation with students of higher education institutions and youth organizations, cooperation with managers and executors of projects of various levels, using the practical experience of teachers on the principles of collegiality in order to improve the quality of education.